2002
DOI: 10.1111/j.1572-0241.2002.05438.x
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of cardiac function in cirrhotic patients treated with transjugular intrahepatic portosystemic shunt (TIPS)

Abstract: Our study demonstrates that nonalcoholic cirrhotic patients, without cardiovascular pathologies, show transient modifications in cardiac dimension and function for 3-6 months after TIPS caused by the increased volume load shunted to the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 24 publications
1
28
0
4
Order By: Relevance
“…Patients with advanced cirrhosis and portal hypertension can develop cardiomyopathy with left ventricular diastolic dysfunction [21] , hyperdynamic state, volume overload, and less commonly portopulmonary hypertension; these conditions can be aggravated with the insertion of TIPS [14,17,[22][23][24] . The placement of TIPS rapidly increases the RV preload and afterload, which can lead to overt heart failure, pulmonary hypertension and death [11,14,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . RA pressure obtained before TIPS could be of value in clinical practice; physicians may elect to abort a TIPS procedure based on this hemodynamic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced cirrhosis and portal hypertension can develop cardiomyopathy with left ventricular diastolic dysfunction [21] , hyperdynamic state, volume overload, and less commonly portopulmonary hypertension; these conditions can be aggravated with the insertion of TIPS [14,17,[22][23][24] . The placement of TIPS rapidly increases the RV preload and afterload, which can lead to overt heart failure, pulmonary hypertension and death [11,14,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . RA pressure obtained before TIPS could be of value in clinical practice; physicians may elect to abort a TIPS procedure based on this hemodynamic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…18 Merli et al have shown a significantly increased cardiac workload and in some cases, abnormal responses, in patients after TIPS insertion. 19 In this issue, Ruiz-del-Arbol et al present novel data that suggests yet another significant complication of impaired ventricular function in cirrhosis. 20 They found that, among a cohort of patients with spontaneous bacterial peritonitis (SBP), those that developed acute renal failure (hepatorenal syndrome) showed significantly less cardiac reserve than those whose renal function remained unimpaired.…”
mentioning
confidence: 99%
“…Various other authors also reported more or less similar findings. The highest prevalence was reported by Merli et al 20 (Table 9). We did not use stress echo in our study, which could have probably underestimated the actual prevalence of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 61%